Development of an Ethnobotany Encyclopedia of Medicinal Plants in Teluk Batang Village, Teluk Batang District as a Biology Learning Resource - Mediani; Ahmad Faisal Amri; Hanum Mukti Rahayu (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a valid ethnobotanical encyclopedia of medicinal plants based on local potential as a learning medium for the Biodiversity topic in Grade X Biology. Using the Research and Development (R&D) method with a 4-D model (Define, Design, Develop, Disseminate), the product was validated by experts in material, media, and language. Validation results indicated high validity: 95.71% from media experts, 91.23% from material experts, and 86.11% from language experts. Student responses were also positive, with a score of 80.42% in small-scale testing and 82.78% in large-scale testing. The final product presents information about medicinal plants in Teluk Batang Village, including local names, scientific names, properties, and chemical compositions, integrated with interactive visuals and QR-coded videos. These findings suggest that the encyclopedia is a valid and engaging alternative learning resource that integrates scientific content with local wisdom.